A Morphological Analysis for the Inclusion of Social Housing Projects in the Centre of Guayaquil, a Restriction or an Opportunity? - Delgado Alina; Torres Juan Carlos (Lodz University of Technology Press, 2023)
Urban centres revitalisation is a task undertaken by the governments of Latin American countries decades ago, following the trends of European nations. The high cost of peri-urban development, the deterioration of urban centres and the sub-use of existing urban infrastructure ignited interest in city centre revitalisation. Guayaquil is no exception to the above. In a city with a continuous expansion of its urban boundaries at a high economic, social and environmental cost, it becomes essential to consider housing projects to revitalise its urban centre. The purpose of this study is to analyse possibilities or restrictions for including social housing projects in the city centre, based on the analysis of existing urban tissues. A combination of methods is used, including the study of concepts, a morphological analysis of urban variables and a walkability assessment. Besides, land use instruments with a social focus are included for promoting and securing land for housing developments to contribute to urban centre revitalisation. Results indicate the relation between urban form, variables and possibilities for urban centre revitalisation through the inclusion of social housing projects. The study concludes with a critical reflection regarding the opportunities or restrictions of the selected approach to include new revitalisation proposals and how the different visions of the city could be integrated and included in the existing urban pattern.
Keywords: urban form; urban centre revitalisation; morphological analysis; land value instruments; forma urbanistyczna; rewitalizacja ośrodków miejskich; analiza morfologiczna; instrumenty wyceny gruntów